A saga of swans: an episode of cultural and natural history. Issue 2 (4th May 2022) - Vernon, Carl J.; Dean, W. Richard J.
Abstract : Mute Swans Cygnus olor were introduced, either deliberately or "self-introduced" to various water bodies from ca 1920 to ca 1965 in the southern parts of South Africa, and in some cases survived for more than a decade. The success of local populations, their survival and subsequent extinctions are discussed, together with possible reasons for their demise. An attempt, on a much smaller scale, to introduce Black Swans Cygnus atratus was also made at about the same time, and this was not at all successful, with no breeding attempts and almost no survivors of initial introductions. The largest number of Mute Swans in one area was at the Kromme River complex in the Eastern Cape Province, where the introduction of the original Mute Swans to the area is fraught with conjecture and speculation. The facts and the dates of the introduction cannot be verified, but the best guess on circumstantial evidence is that the swans arrived on a dam near the Kromme River via an escape from a crate on deck that was washed overboard from a ship during a storm. Subsequent introductions of Mute Swans to Groenvlei (Goukamma Nature Reserve) and the Wilderness-Sedgefield-Lakes-Complex in the Western Cape and to other localities in that province were of swans caught at the Kromme and other waters. None of the populations of swans survived beyond the early 1980s, and their demise is as mysterious as are the origins of the founder population at the Kromme River.